Theoretic and Methodological Approaches Towards the Application of Mixed Methods in the Discipline of International Relations - Aylin Ece Çiçek; Damla Cihangir Tetik (Siyasal: Journal of Political Sciences)
Discussions regarding the conduct of scientific inquiry have existed throughout history. Questions of how to uncover the truth and achieve reliable and valid scientific conclusions, all under the umbrella of objectivity, have led the sciences to evolve in a systematic manner. Hitherto, the general leniency within this conversation has been directed at the hard sciences; however, the Social Sciences have also recently been on the receiving end of paradigmatic shifts in methodologies. Since the behavioral revolution, the conduct of many disciplines under the Social Sciences has slowly moved towards a more quantitative outlook on the path of uncovering social phenomena. Such an alteration in methodology has its benefits as well as certain handicaps when dealing with abstract social concepts and notions which are difficult to quantify. This is especially the case for the discipline of International Relations (IR), where data are of both a qualitative and quantitative nature. Thus, the aims of this study are threefold: first, the study will present a brief summary of the historical and scientific evolution of methods in the discipline of IR; secondly, it will describe the current situation in which scientific inquiry is conducted, focusing on mixed method approaches; and third, it will deal with the different methodological approaches of MM designs established above by highlighting their strengths and weaknesses, particularly in the discipline of IR. Hence, this study aims to contribute both to the literatures of the disciplines of IR and of methodology in Social Sciences.